THE PERSONAL PSYCHOLOGICAL SECURITY IN THE CONTEXT OF THE WORK ENVIRONMENT CHANGES - Papoyan , V. R.; Zurabyan , A. M. (Modern Psychology, 2025)
The structure of the problem of personal psychological security insurance in the context of the work environment changes is presented in the article. The structural components of the person’s psychological security in the work environ- ment are interpreted in detail and the observation of the conflict between person and external environment in margins of macro and microenvironments. In the result of the theoretical analysis, the connection between psychological security, psychological health, personal orientation, the subjective reflection of objective reality, and emotional component is emphasized in details clarifying the basis of the shape of the danger. Relative commonalities of the work conditions are revealed at the personal level when parallels are drawn between the work environment and the psychological side of the security.